Association of Depression in Patients with Fibromyalgia Syndrome - Hussain Ahmad, Yousaf Gul, Sher Ayub Dawar, Qasim Riaz, Kiramat Ullah, Asif Kamal (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Fibromyalgia syndrome (FMS) is a chronic pain condition, frequently accompanied by psychological distress, including depression. Objectives: This study assessed association between depression and FMS, including its incidence, severity and its impact on quality of life. Methods: A cross-sectional investigation comprised 96 individuals diagnosed with fibromyalgia at Mufti Mehmood Memorial Teaching Hospital, Dera Ismail Khan in 2021-22. Two questionnaires were used to assess their symptoms i.e. Widespread Pain Index and Symptom Severity Scale score. Depression was evaluated in patients through Hospital Anxiety and Depression Scale. Results: We found that a significant proportion (p<0.05) had WPI score of more than 7 (48/96; 50%) and 76.04% patients had SSS score (p<0.05) of more than 5, confirming the depression in patients with fibromyalgia. Overall results suggested that the FMS affected patients suffered from moderate to severe levels of depression (47.91%) with HADS scores of 11-21 range Practical implication: The study will enable the patients and psychiatrics to diagnose the underlying causes of depression in patients affected with fibromyalgia. Conclusion: It was concluded that depression was the common comorbidity in patients with fibromyalgia; however, the exact link between the two conditions is not fully understood. Effective management of depression is crucial in improving the quality of life with fibromyalgia, as depression can exacerbate pain and other symptoms. Keywords: Cognitive dysfunction; Depression; Fibromyalgia; Pain.